Comprehensive profiling analysis of the N6-methyladenosine-modified circular RNA transcriptome in cultured cells infected with Marek’s disease virus - Aijun Sun (Nature Portfolio, 2021)
Abstract Marek’s disease virus (MDV) induces severe immunosuppression and lymphomagenesis in the chicken, its natural host, and results in a condition that investigated the pathogenesis of MDV and have begun to focus on the expression profiling of circular RNAs (circRNAs). However, little is known about how the expression of circRNAs is referred to as Marek’s disease. Previous reports have is regulated during MDV replication. Here, we carried out a comprehensive profiling analysis of N6-methyladenosine (m6A) modification on the circRNA transcriptome in infected and uninfected chicken embryonic fibroblast (CEF) cells. Methylated RNA immunoprecipitation sequencing (MeRIP-Seq) revealed that m6A modification was highly conserved in circRNAs. Comparing to the uninfected group, the number of peaks and conserved motifs were not significantly different in cells that were infected with MDV, although reduced abundance of circRNA m6A modifications. However, gene ontology and Kyoto encyclopedia of genes and genomes (KEGG) pathway analyses revealed that the insulin signaling pathway was associated with the regulation of m6A modified circRNAs in MDV infection. This is the first report to describe alterations in the transcriptome-wide profiling of m6A modified circRNAs in MDV-infected CEF cells.